Climate Change: Towards Compensating Africa for Economic Growth and Development by Industrialized Countries - Monaheng Mahlatsi (Journal of Social and Development Sciences, 2018)
On one hand, anthropogenic climate change is real and affecting the world economy in general and Africa in particular. On the other hand, the policy of climate change adaptation as the solution to the problem of climate change is seriously unsuccessful in Africa. Even though climate change is affecting the whole world, Africa is the most vulnerable continent that is economically affected. This is due to a variety of interconnected consequences of climate change such as droughts, floods, desertification, diseases and poor agricultural system including other unknown factors. This article focuses on challenges facing the implementation of climate change adaptation policy in Africa. The implementation of the policy of mitigation of greenhouse gas emissions will not be discussed. The aim of the article is to investigate the underlying implications of climate change adaptation policy that hamper smooth growth and development of the African economy. To achieve this aim, the theoretical research method will be utilized. This article concludes that Africa cannot afford to adapt to climate change because of its extreme poverty and will remain economically poor and suffer the consequences of climate change if industrialized countries are reluctant to compensate it. Therefore, the article argues that industrialized countries have a moral duty to compensate Africa for the harm they have caused through industrialization. The compensation will boost the African economy that is necessary for climate change adaptation.